Preparation method and application of gradient polymerized solid-state battery electrode

By introducing a gradient distribution of NASICON inorganic solid electrolyte into the solid-state battery electrode material, the ring-open polymerization of ring ether-based polymer electrolytes is suppressed, and the gradient polymerization of ring ether-based polymer electrolytes in the electrode is achieved, solving the problem of poor electrode reaction kinetics in solid-state batteries under large-scale conditions, and significantly improving the performance of the battery.

CN119627050AActive Publication Date: 2025-03-14SHANGHAI HANHANG TECH CO LTD

Patent Information

Application Number
CN202510150986.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-11
Publication Date
2025-03-14
Estimated Expiration
2045-02-11

AI Technical Summary

Technical Problem

Solid-state batteries have poor electrochemical reaction kinetics of electrodes under large-scale conditions, low utilization rate of active substances, poor rate performance and cycle stability.

Method used

By laying the NASICON type inorganic solid electrolyte Na3Zr2Si2PO12 with gradient distribution in the electrode material, the initiator in the electrolyte precursor solution is inhibited from initiating the ring-open polymerization reaction of the ring-ether-based polymer electrolyte in the electrode, and the gradient polymerization of the ring-ether-based polymer electrolyte in the electrode is realized.

Benefits of technology

The concentration polarization generated by the solid-state battery electrode during the large-scale charging and discharging process is reduced, the ion transport dynamics within the electrode are improved, the deep active substances are fully utilized, and the interface stability, magnification characteristics and cyclic stability of the solid-state battery are significantly improved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a gradient polymerized solid-state battery electrode, and belongs to the technical field of chemical power sources. The method specifically comprises the following steps that NASICON type inorganic solid-state electrolyte Na3Zr2Si2PO12 is distributed in an electrode material in a gradient mode to prepare a pole piece, an electrolyte precursor solution containing cyclic ether monomers and an initiator is injected into the pole piece, the NASICON type inorganic solid-state electrolyte Na3Zr2Si2PO12 distributed in the gradient mode inhibits the action of the initiator and the cyclic ether monomers, and the cyclic ether monomers and the cyclic ether monomers are separated from each other. The gradient polymerization of the cyclic ether-based polymer electrolyte in the electrode is realized, the gradient polymerized solid-state battery electrode is obtained, and the additive amount gradient of the NASICON type inorganic solid-state electrolyte Na3Zr2Si2PO12 is reduced in the direction from the near current collector to the far away from the current collector. The invention provides an innovative electrode scheme for the realization of a high-power and high-cycle-stability solid-state battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of chemical power sources, and in particular relates to a preparation method and application of a gradient polymerized solid-state battery electrode. Background Art

[0002] Solid-state batteries, especially those prepared based on the in-situ polymerization method of electrolytes, can significantly improve the safety of batteries and are an important direction for the development of next-generation secondary batteries. Usually, during the charge and discharge process, especially under high-rate conditions, the electrochemical reaction kinetics of the positive and negative electrodes of alkali metal ion secondary batteries based on liquid electrolytes have large gradient changes in the longitudinal direction, that is, the reaction kinetics of the active material layer close to the current collector is poor, while the reaction kinetics of the active material layer far from the current collector is high. This characteristic will significantly affect the utilization rate of active materials, rate performance and cycle stability of secondary batteries. Polymer electrolytes prepared based on the in-situ polymerization method often have the characteristics of high polymerization degree and relatively low ionic conductivity, and the uniformity of the electrochemical reaction kinetics of solid-state battery electrodes in the longitudinal direction will be further reduced. In view of the electrode reaction kinetics characteristics of solid-state batteries, constructing a polymer electrolyte system with a gradient change in polymerization degree inside the electrode is of great significance to improving the utilization rate of active materials, interface stability, rate performance and cycle stability of solid-state batteries. Summary of the invention

[0003] In order to solve the technical problems of poor electrode electrochemical reaction kinetics, low utilization rate of active materials, poor rate performance and cycle stability of in-situ polymerization solid-state batteries under high rate conditions (≥1C), the present invention provides a preparation method and application of solid-state battery electrodes with gradient polymerization characteristics, using NASICON inorganic solid electrolyte Na3Zr2Si2PO 12 The strong Lewis acid-base interaction between (NZSP) and the initiator inhibits the ring-opening polymerization of cyclic ether monomers and realizes gradient control of the polymerization degree of the polymer electrolyte.

[0004] In order to achieve the above object, the present invention adopts the following technical solutions:

[0005] A method for preparing a gradient polymerized solid-state battery electrode comprises the following steps: adding different mass fractions of NASICON inorganic solid electrolyte Na3Zr2Si2PO4 into the electrode material. 12 Prepare several portions of slurry, and then coat several portions of slurry layer by layer on the current collector to make the NASICON inorganic solid electrolyte Na3Zr2Si2PO 12The amount of addition decreases gradually from the direction close to the current collector to the direction away from the current collector, and then the electrode is dried, rolled, and cut to obtain an electrode. An electrolyte precursor solution containing a cyclic ether monomer and an initiator is injected into the electrode to form a gradient distributed NASICON-type inorganic solid electrolyte Na3Zr2Si2PO 12 The reaction between the initiator and the cyclic ether monomer is inhibited to realize the gradient polymerization of the cyclic ether-based polymer electrolyte in the electrode, thereby obtaining a gradient polymerized solid-state battery electrode.

[0006] Furthermore, the NASICON inorganic solid electrolyte Na3Zr2Si2PO 12 The mass range of the gradient distribution in the electrode material from close to the current collector to far away from the current collector is 0.1wt-2wt%.

[0007] Furthermore, the cyclic ether monomer includes one or more combinations of tetrahydrofuran, 1,3-dioxolane, 1,3,5-trioxane, 1,3-dioxane, epoxy-terminated linear siloxane and epoxy-terminated cage-type polysilsesquioxane.

[0008] Furthermore, the initiator includes a combination of one or more of a sodium salt initiator, a lithium salt initiator, an aluminum salt initiator, a tin salt initiator, a zinc salt initiator, a magnesium salt initiator, and a scandium salt initiator.

[0009] Furthermore, the cyclic ether monomer accounts for 40%-80% of the volume of the electrolyte, and the selection of this numerical range belongs to the conventional technical means in the field.

[0010] Furthermore, the concentration of the initiator in the electrolyte is 0.1-1 mol / L, and the selection of this numerical range belongs to the conventional technical means in the art.

[0011] Furthermore, the electrode material includes an active material, a conductive agent and a binder that are uniformly mixed.

[0012] Furthermore, the electrolyte precursor solution also includes a solvent, an ion salt and an additive, and the ion salt is a lithium salt, a sodium salt or a potassium salt.

[0013] Furthermore, after the electrolyte precursor solution is injected into the electrode, it is left to stand at room temperature or under heating conditions, and the cyclic ether monomer undergoes ring-opening polymerization under the action of the initiator to form a gradient-distributed NASICON-type inorganic solid electrolyte Na3Zr2Si2PO 12 The initiation effect of the initiator is suppressed to realize the gradient polymerization of the cyclic ether-based polymer electrolyte in the electrode.

[0014] An application of a solid-state battery electrode prepared by the preparation method, wherein the solid-state battery electrode is applied to a positive electrode and / or a negative electrode of a lithium-ion battery, a positive electrode and / or a negative electrode of a sodium-ion battery, or a positive electrode and / or a negative electrode of a potassium-ion battery.

[0015] Compared with the prior art, the present invention has the following beneficial effects:

[0016] The present invention arranges NASICON inorganic solid electrolyte Na3Zr2Si2PO4 in a gradient distribution in the electrode material. 12 , inhibiting the ring-opening polymerization reaction of cyclic ether monomers initiated by the initiator in the electrolyte precursor solution, thereby realizing the gradient polymerization of cyclic ether-based polymer electrolytes in the electrode. Compared with solid-state batteries prepared based on traditional in-situ polymerization methods, the cyclic ether-based polymer electrolytes in the new solid-state battery electrodes show a change in the degree of polymerization gradient in the longitudinal direction. From the surface of the current collector to the direction away from the current collector, the degree of polymerization of the cyclic ether-based polymer electrolyte increases in a gradient manner, and the ionic conductivity of the cyclic ether-based polymer electrolyte inside the electrode gradually increases from the surface of the electrode to the surface of the current collector. This characteristic can reduce the concentration polarization generated by the solid-state battery electrode during high-rate charge and discharge, improve the ion transfer kinetics inside the electrode, realize the full utilization of deep-layer active substances, and significantly improve the interface stability, rate characteristics and cycle stability of solid-state batteries. DETAILED DESCRIPTION

[0018] The technical solutions in the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0019] Embodiment 1:

[0020] A method for preparing a gradient polymerized solid-state sodium ion battery positive electrode comprises the following steps:

[0021] Step 1, 96 parts of positive electrode active material sodium vanadium phosphate Na3V2(PO4)3, 2 parts of conductive agent Super P, and 2 parts of binder polyvinylidene fluoride PVDF are uniformly mixed to form a positive electrode material and divided into 4 parts, and inorganic solid electrolyte NZSP accounting for 0.1%, 0.3%, 0.6% and 1.0% of the mass fraction of the positive electrode material are added to the 4 parts of positive electrode material, respectively, and wet mixing is performed to obtain 4 parts of liquid slurries with different contents of inorganic solid electrolyte NZSP;

[0022] Step 2: Apply the 4 portions of liquid slurry prepared in step 1 layer by layer on the surface of the current collector, so that the amount of the inorganic solid electrolyte NZSP added decreases gradually from the direction close to the current collector to the direction away from the current collector, and then dry, roll and cut to obtain a positive electrode sheet with a gradient distribution of NZSP;

[0023] Step 3, sodium salt sodium perchlorate NaClO4, film-forming additive fluoroethylene carbonate FEC (accounting for 1wt% of the total mass of the electrolyte precursor solution), initiator sodium hexafluorophosphate NaPF6 (concentration of 0.5mol / L), solvent ethylene glycol dimethyl ether DME and cyclic ether monomer 1,3-dioxolane DOL (the volume ratio of DME and DOL is 1:1) are mixed uniformly to prepare an electrolyte precursor solution with a sodium salt NaClO4 concentration of 1mol / L;

[0024] Step 4: injecting the electrolyte precursor solution prepared in step 3 into the positive electrode sheet with gradient distribution of NZSP prepared in step 2 under vacuum;

[0025] Step 5. After standing at room temperature for 12 hours, the cyclic ether monomer DOL undergoes ring-opening polymerization under the action of the initiator NaPF6. The gradient-distributed inorganic solid electrolyte NZSP inhibits the initiation effect of the initiator NaPF6, achieving gradient polymerization of the DOL monomer in the electrode, and obtaining a solid-state sodium ion battery positive electrode with gradient polymerization characteristics.

[0026] Embodiment 2:

[0027] A method for preparing a gradient polymerized solid-state sodium ion battery negative electrode comprises the following steps:

[0028] Step 1, 90 parts of negative electrode active material hard carbon, 5 parts of conductive agent Super P, and 5 parts of binder sodium carboxymethyl cellulose CMC are uniformly mixed to form a negative electrode material and divided into 4 parts, and inorganic solid electrolyte NZSP accounting for 0.5%, 1.0%, 1.5% and 2.0% of the mass fraction of the negative electrode material are added to the 4 parts of negative electrode materials, respectively, and wet mixed to obtain 4 parts of liquid slurries with different contents of inorganic solid electrolyte NZSP;

[0029] Step 2: Apply the 4 portions of liquid slurry prepared in step 1 layer by layer on the surface of the current collector, so that the amount of the inorganic solid electrolyte NZSP added decreases gradually from the direction close to the current collector to the direction away from the current collector, and then dry, roll and cut to obtain a negative electrode sheet with a gradient distribution of NZSP;

[0030] Step 3, sodium salt sodium perchlorate NaClO4, film-forming additive fluoroethylene carbonate FEC (accounting for 1wt% of the total mass of the electrolyte precursor solution), initiator sodium hexafluorophosphate NaPF6 (concentration of 0.5mol / L), solvent ethylene glycol dimethyl ether DME and cyclic ether monomer 1,3-dioxolane DOL (the volume ratio of DME and DOL is 1:1) are mixed uniformly to prepare an electrolyte precursor solution with a sodium salt NaClO4 concentration of 1mol / L;

[0031] Step 4: injecting the electrolyte precursor solution prepared in step 3 into the negative electrode sheet with gradient distribution of NZSP prepared in step 2 under vacuum;

[0032] Step 5. After standing at room temperature for 12 hours, the cyclic ether monomer DOL undergoes ring-opening polymerization under the action of the initiator NaPF6. The gradient-distributed inorganic solid electrolyte NZSP inhibits the initiation effect of the initiator NaPF6, achieving gradient polymerization of the DOL monomer in the electrode, and obtaining a solid-state sodium ion battery negative electrode with gradient polymerization characteristics.

[0033] Embodiment 3:

[0034] The positive electrode sheet with gradient distribution of NZSP prepared in step 2 of Example 1, a separator and a button half-cell with sodium metal are assembled, and the electrolyte precursor solution prepared in step 3 of Example 1 is added dropwise. The mixture is allowed to stand at room temperature for 12 hours. The cyclic ether monomer DOL undergoes ring-opening polymerization under the action of the initiator NaPF6. The inorganic solid electrolyte NZSP with gradient distribution in the positive electrode sheet inhibits the initiation effect of the initiator NaPF6, thereby realizing the gradient polymerization of the DOL monomer in the positive electrode, and obtaining a solid-state sodium ion positive electrode half-cell with gradient polymerization characteristics. The battery has a capacity retention rate of 98% after 2500 cycles at a voltage range of 2.5-3.8V and a 1C rate, and the initial reversible capacity at a 1C rate reaches 95% of the reversible capacity at a 0.1C rate.

[0035] Embodiment 4:

[0036] The negative electrode plate with gradient distribution of NZSP prepared in step 2 of Example 2, a separator and a button half-cell with sodium metal are assembled, and the electrolyte precursor solution prepared in step 3 of Example 2 is added dropwise. The mixture is allowed to stand at room temperature for 12 hours. The cyclic ether monomer DOL undergoes ring-opening polymerization under the action of the initiator NaPF6. The inorganic solid electrolyte NZSP with gradient distribution in the negative electrode plate inhibits the initiation effect of the initiator NaPF6, thereby achieving gradient polymerization of the DOL monomer in the negative electrode, and obtaining a solid-state sodium ion negative electrode half-cell with gradient polymerization characteristics. The battery has a capacity retention rate of 97% after 2500 cycles at a voltage range of 0.1-1.5V and a 1C rate, and the initial reversible capacity at a 1C rate reaches 96% of the reversible capacity at a 0.1C rate.

[0037] Embodiment 5:

[0038] The positive electrode sheet with gradient distribution of NZSP prepared in step 2 of Example 1, the separator and the negative electrode sheet with gradient distribution of NZSP prepared in step 2 of Example 2 are assembled into a button-type full battery, and the electrolyte precursor solution prepared in step 3 of Example 1 is added dropwise. The mixture is allowed to stand for 12 hours at room temperature, and the cyclic ether monomer DOL undergoes ring-opening polymerization under the action of the initiator NaPF6 to obtain a solid-state sodium ion full battery with gradient polymerization characteristics. The battery has a capacity retention rate of 95% when cycled 2500 times at a voltage rate of 1C in the voltage range of 2.5-3.8V, the initial reversible capacity at a rate of 1C reaches 96% of the reversible capacity at a rate of 0.1C, and the initial reversible capacity at a rate of 5C reaches 90% of the reversible capacity at a rate of 0.1C.

[0039] Embodiment 6:

[0040] A method for preparing a gradient polymerized solid-state lithium-ion battery positive electrode comprises the following steps:

[0041] Step 1, 96 parts of positive electrode active material lithium iron phosphate LiFePO4, 2 parts of conductive agent Super P, and 2 parts of binder polyvinylidene fluoride PVDF are uniformly mixed to form a positive electrode material and divided into 4 parts, and inorganic solid electrolyte NZSP accounting for 0.2%, 0.4%, 0.6% and 0.8% of the mass fraction of the positive electrode material are added to the 4 parts of positive electrode material, respectively, and wet mixed to obtain 4 parts of liquid slurries with different contents of inorganic solid electrolyte NZSP;

[0042] Step 2: Apply the 4 portions of liquid slurry prepared in step 1 layer by layer on the surface of the current collector, so that the amount of the inorganic solid electrolyte NZSP added decreases gradually from the direction close to the current collector to the direction away from the current collector, and then dry, roll and cut to obtain a positive electrode sheet with a gradient distribution of NZSP;

[0043] Step 3, lithium salt bistrifluoromethylsulfonyl imide lithium LiTFSI, film-forming additive fluoroethylene carbonate FEC (accounting for 2% of the total mass of the electrolyte), initiator lithium difluorooxalatoborate LiODFB (concentration of 0.5 mol / L), solvent ethylene glycol dimethyl ether DME and cyclic ether monomer 1,3,5-trioxane TXE (the volume ratio of TXE and DME is 1:1) are mixed uniformly to prepare an electrolyte precursor solution with a lithium salt LiTFSI concentration of 1 mol / L;

[0044] Step 4: injecting the electrolyte precursor solution prepared in step 3 into the positive electrode sheet with gradient distribution of NZSP prepared in step 2 under vacuum;

[0045] Step 5. Standing at 60°C for 12 hours, the cyclic ether monomer TXE undergoes ring-opening polymerization under the action of the initiator LiODFB, and the gradient-distributed inorganic solid electrolyte NZSP inhibits the initiation effect of the initiator LiODFB, achieving gradient polymerization of the TXE monomer in the electrode, and obtaining a solid-state lithium-ion battery positive electrode with gradient polymerization characteristics.

[0046] Embodiment 7:

[0047] A method for preparing a gradient polymerized solid-state lithium-ion battery negative electrode comprises the following steps:

[0048] Step 1, 90 parts of negative electrode active material graphite, 5 parts of conductive agent Super P, and 5 parts of binder sodium carboxymethyl cellulose CMC are uniformly mixed to form a negative electrode material and divided into 4 parts, and inorganic solid electrolyte NZSP accounting for 0.5%, 1.0%, 1.5% and 2.0% of the mass fraction of the negative electrode material are added to the 4 parts of negative electrode materials, respectively, and wet mixed to obtain 4 parts of liquid slurries with different contents of inorganic solid electrolyte NZSP;

[0049] Step 2: Apply the 4 portions of liquid slurry prepared in step 1 layer by layer on the surface of the current collector, so that the amount of the inorganic solid electrolyte NZSP added decreases gradually from the direction close to the current collector to the direction away from the current collector, and then dry, roll and cut to obtain a negative electrode sheet with a gradient distribution of NZSP;

[0050] Step 3, lithium salt bistrifluoromethylsulfonyl imide lithium LiTFSI, film-forming additive fluoroethylene carbonate FEC (accounting for 2% of the total mass of the electrolyte), initiator lithium difluorooxalatoborate LiODFB (concentration of 0.5 mol / L), solvent ethylene glycol dimethyl ether DME and cyclic ether monomer 1,3,5-trioxane TXE (the volume ratio of TXE and DME is 1:1) are mixed uniformly to prepare an electrolyte precursor solution with a lithium salt LiTFSI concentration of 1 mol / L;

[0051] Step 4: injecting the electrolyte precursor solution prepared in step 3 into the negative electrode sheet with gradient distribution of NZSP prepared in step 2 under vacuum;

[0052] Step 5. Standing at 60°C for 12 hours, the cyclic ether monomer TXE undergoes ring-opening polymerization under the action of the initiator LiODFB, and the gradient-distributed inorganic solid electrolyte NZSP inhibits the initiation effect of the initiator LiODFB, achieving gradient polymerization of the TXE monomer in the electrode, and obtaining a solid-state lithium-ion battery negative electrode with gradient polymerization characteristics.

[0053] Embodiment 8:

[0054] The positive electrode sheet, separator and lithium metal with gradient distribution of NZSP prepared in step 2 of Example 6 are assembled into a button half-cell, and the electrolyte precursor solution prepared in step 3 of Example 6 is added dropwise. The mixture is allowed to stand at 60°C for 12 hours. The cyclic ether monomer TXE undergoes ring-opening polymerization under the action of the initiator LiODFB, and the inorganic solid electrolyte NZSP with gradient distribution inhibits the initiation effect of the initiator LiODFB, thereby realizing the gradient polymerization of the TXE monomer in the electrode, and obtaining a solid-state lithium ion positive electrode half-cell with gradient polymerization characteristics. The battery has a capacity retention rate of 98% after 5000 cycles at a voltage range of 2.5-4.0 V and a 2C rate, and the initial reversible capacity at a 2C rate reaches 98% of the reversible capacity at a 0.1C rate.

[0055] Embodiment 9:

[0056] The negative electrode sheet, separator and lithium metal with gradient distribution of NZSP prepared in step 2 of Example 7 are assembled into a button half-cell, and the electrolyte precursor solution prepared in step 3 of Example 7 is added dropwise. The mixture is allowed to stand at 60° C. for 12 h. The cyclic ether monomer TXE undergoes ring-opening polymerization under the action of the initiator LiODFB. The inorganic solid electrolyte NZSP with gradient distribution inhibits the initiation effect of the initiator LiODFB, thereby realizing the gradient polymerization of the TXE monomer in the electrode, and obtaining a solid-state lithium ion negative electrode half-cell with gradient polymerization characteristics. The battery has a capacity retention rate of 95% after 5000 cycles at a voltage range of 0.05-1.5V and a 2C rate, and the initial reversible capacity at a 2C rate reaches 97% of the reversible capacity at a 0.1C rate.

[0057] Embodiment 10:

[0058] The positive electrode sheet and separator with gradient distribution of NZSP prepared in step 2 of Example 6 and the negative electrode sheet with gradient distribution of NZSP prepared in step 2 of Example 7 were assembled into a button-type full battery, and the electrolyte precursor solution prepared in step 3 of Example 6 was added dropwise. The mixture was allowed to stand at 60° C. for 12 h, and the cyclic ether monomer TXE underwent ring-opening polymerization under the action of the initiator LiODFB. The inorganic solid electrolyte NZSP with gradient distribution inhibited the initiation effect of the initiator LiODFB, thereby realizing the gradient polymerization of the TXE monomer in the electrode, and obtaining a solid-state lithium-ion full battery with gradient polymerization characteristics. The battery had a capacity retention rate of 95% after 5000 cycles at a 2C rate in a voltage range of 2.5-4.0 V, the initial reversible capacity at a 2C rate reached 95% of the reversible capacity at a 0.1C rate, and the initial reversible capacity at a 5C rate reached 85% of the reversible capacity at a 0.1C rate.

[0059] Comparative Example 1:

[0060] A method for preparing a positive electrode of a solid-state sodium ion battery comprises the following steps:

[0061] Step 1: Wet-mix 96 parts of positive electrode active material sodium vanadium phosphate Na3V2(PO4)3, 2 parts of conductive agent Super P, and 2 parts of binder polyvinylidene fluoride PVDF to obtain positive electrode slurry;

[0062] Step 2: coating the positive electrode slurry prepared in step 1 on the surface of the current collector, and then drying, rolling and cutting to obtain positive electrode sheets;

[0063] Step 3, sodium salt sodium perchlorate NaClO4, film-forming additive fluoroethylene carbonate FEC (accounting for 1wt% of the total mass of the electrolyte precursor solution), initiator sodium hexafluorophosphate NaPF6 (concentration of 0.5mol / L), solvent ethylene glycol dimethyl ether DME and cyclic ether monomer 1,3-dioxolane DOL (the volume ratio of DME and DOL is 1:1) are mixed uniformly to prepare an electrolyte precursor solution with a sodium salt NaClO4 concentration of 1mol / L;

[0064] Step 4: injecting the electrolyte precursor solution prepared in step 3 into the positive electrode sheet prepared in step 2 under vacuum;

[0065] Step 5: After standing at room temperature for 12 hours, the cyclic ether monomer DOL undergoes ring-opening polymerization under the action of the initiator NaPF6 to obtain a solid-state sodium ion battery positive electrode.

[0066] Comparative Example 2:

[0067] A method for preparing a solid-state sodium ion battery negative electrode comprises the following steps:

[0068] Step 1: Wet-mix 90 parts of negative electrode active material hard carbon, 5 parts of conductive agent Super P, and 5 parts of binder sodium carboxymethyl cellulose CMC to obtain a negative electrode slurry;

[0069] Step 2: coating the negative electrode slurry prepared in step 1 on the surface of the current collector, and then drying, rolling and cutting to obtain negative electrode sheets;

[0070] Step 3, sodium salt sodium perchlorate NaClO4, film-forming additive fluoroethylene carbonate FEC (accounting for 1wt% of the total mass of the electrolyte precursor solution), initiator sodium hexafluorophosphate NaPF6 (concentration of 0.5mol / L), solvent ethylene glycol dimethyl ether DME and cyclic ether monomer 1,3-dioxolane DOL (the volume ratio of DME and DOL is 1:1) are mixed uniformly to prepare an electrolyte precursor solution with a sodium salt NaClO4 concentration of 1mol / L;

[0071] Step 4: injecting the electrolyte precursor solution prepared in step 3 into the negative electrode sheet prepared in step 2 under vacuum;

[0072] Step 5: After standing at room temperature for 12 hours, the cyclic ether monomer DOL undergoes ring-opening polymerization under the action of the initiator NaPF6 to obtain a solid-state sodium ion battery negative electrode.

[0073] Comparative Example 3:

[0074] The positive electrode sheet, separator, and sodium metal prepared in Comparative Example 1 were assembled into a button half-cell, and the electrolyte precursor solution prepared in Comparative Example 1 was added dropwise. The cells were allowed to stand at room temperature for 12 hours to obtain a solid-state sodium ion positive electrode half-cell. The cell retained 50% of its capacity after 2500 cycles at a voltage range of 2.5-3.8V and a rate of 1C. The initial reversible capacity at a rate of 1C was only 75% of the reversible capacity at a rate of 0.1C.

[0075] Comparative Example 4:

[0076] The negative electrode sheet, separator, and sodium metal prepared in Comparative Example 2 were assembled into a button half-cell, and the electrolyte precursor solution prepared in Comparative Example 2 was added dropwise. The cells were allowed to stand at room temperature for 12 hours to obtain a solid-state sodium ion negative electrode half-cell. The cell retained 55% of its capacity after 2500 cycles at a voltage range of 0.1-1.5V and a rate of 1C, and the initial reversible capacity at a rate of 1C was only 65% ​​of the reversible capacity at a rate of 0.1C.

[0077] Comparative Example 5:

[0078] The positive electrode sheet and separator prepared in Comparative Example 1 and the negative electrode sheet prepared in Comparative Example 2 are assembled into a button-type full battery, and the electrolyte precursor solution prepared in Comparative Example 1 is added dropwise. The battery is left standing at room temperature for 12 hours to obtain a solid-state sodium ion full battery. The battery has a capacity retention rate of 45% when cycled 2500 times at a voltage range of 2.5-3.8V at a 1C rate, and the initial reversible capacity at a 1C rate is only 72% of the reversible capacity at a 0.1C rate, and the initial reversible capacity at a 5C rate is only 30% of the reversible capacity at a 0.1C rate.

[0079] Comparative Example 6:

[0080] A method for preparing a positive electrode of a solid-state lithium-ion battery comprises the following steps:

[0081] Step 1: Wet-mix 96 parts of positive electrode active material lithium iron phosphate LiFePO4, 2 parts of conductive agent Super P, and 2 parts of binder polyvinylidene fluoride PVDF to obtain positive electrode slurry;

[0082] Step 2: coating the positive electrode slurry prepared in step 1 on the surface of the current collector, and then drying, rolling and cutting to obtain positive electrode sheets;

[0083] Step 3, lithium salt bistrifluoromethylsulfonyl imide lithium LiTFSI, film-forming additive fluoroethylene carbonate FEC (accounting for 2% of the total mass of the electrolyte), initiator lithium difluorooxalatoborate LiODFB (concentration of 0.5 mol / L), solvent ethylene glycol dimethyl ether DME and cyclic ether monomer 1,3,5-trioxane TXE (the volume ratio of TXE and DME is 1:1) are mixed uniformly to prepare an electrolyte precursor solution with a lithium salt LiTFSI concentration of 1 mol / L;

[0084] Step 4: injecting the electrolyte precursor solution prepared in step 3 into the positive electrode sheet prepared in step 2 under vacuum;

[0085] Step 5: Standing at 60° C. for 12 hours, the cyclic ether monomer TXE undergoes ring-opening polymerization under the action of the initiator LiODFB to obtain a solid-state lithium-ion battery positive electrode.

[0086] Comparative Example 7:

[0087] A method for preparing a negative electrode of a solid-state lithium-ion battery comprises the following steps:

[0088] Step 1: Wet-mix 90 parts of negative electrode active material graphite, 5 parts of conductive agent Super P, and 5 parts of binder sodium carboxymethyl cellulose CMC to obtain a negative electrode slurry;

[0089] Step 2: coating the negative electrode slurry prepared in step 1 on the surface of the current collector, and then drying, rolling and cutting to obtain negative electrode sheets;

[0090] Step 3, lithium salt bistrifluoromethylsulfonyl imide lithium LiTFSI, film-forming additive fluoroethylene carbonate FEC (accounting for 2% of the total mass of the electrolyte), initiator lithium difluorooxalatoborate LiODFB (concentration of 0.5 mol / L), solvent ethylene glycol dimethyl ether DME and cyclic ether monomer 1,3,5-trioxane TXE (the volume ratio of TXE and DME is 1:1) are mixed uniformly to prepare an electrolyte precursor solution with a lithium salt LiTFSI concentration of 1 mol / L;

[0091] Step 4: injecting the electrolyte precursor solution prepared in step 3 into the negative electrode sheet prepared in step 2 under vacuum;

[0092] Step 5: Standing at 60° C. for 12 hours, the cyclic ether monomer TXE undergoes ring-opening polymerization under the action of the initiator LiODFB to obtain a solid-state lithium-ion battery negative electrode.

[0093] Comparative Example 8:

[0094] The positive electrode sheet, separator and lithium metal prepared in Comparative Example 6 were assembled into a button half-cell, and the electrolyte precursor solution prepared in Comparative Example 6 was added dropwise, and the mixture was left at 60°C for 12 hours to obtain a solid-state lithium-ion positive electrode half-cell. The battery had a capacity retention rate of 60% after 5000 cycles at a 2C rate in a voltage range of 2.5-4.0V, and the initial reversible capacity at a 2C rate was only 65% ​​of the reversible capacity at a 0.1C rate.

[0095] Comparative Example 9:

[0096] The negative electrode sheet, separator and lithium metal prepared in Comparative Example 7 were assembled into a button half-cell, and the electrolyte precursor solution prepared in Comparative Example 7 was added dropwise, and the mixture was left at 60°C for 12 hours to obtain a solid-state lithium-ion negative electrode half-cell. The battery had a capacity retention rate of 55% after 5000 cycles at a voltage range of 0.05-1.5V and a 2C rate, and the initial reversible capacity at a 2C rate was only 60% of the reversible capacity at a 0.1C rate.

[0097] Comparative Example 10:

[0098] The positive electrode sheet and separator prepared in Comparative Example 6 and the negative electrode sheet prepared in Comparative Example 7 are assembled into a button-type full battery, and the electrolyte precursor solution prepared in Comparative Example 6 is added dropwise, and the mixture is left at 60°C for 12 hours to obtain a solid-state lithium-ion full battery. The battery has a capacity retention rate of 40% after 5000 cycles at a 2C rate in a voltage range of 2.5-4.0V, and the initial reversible capacity at a 2C rate is only 55% of the reversible capacity at a 0.1C rate, and the initial reversible capacity at a 5C rate is only 25% of the reversible capacity at a 0.1C rate.

[0099] In summary, compared with the traditional solid-state batteries prepared in Comparative Examples 5 and 10, the solid-state batteries with gradient polymerization characteristics prepared in Examples 5 and 10 show excellent electrochemical performance, and the discharge specific capacity and cycle stability at the same rate are significantly improved, which fully demonstrates the superiority of the solid-state batteries with gradient polymerization characteristics.

[0100] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for preparing a gradient polymerized solid-state battery electrode, characterized in that: The following steps are involved: Different mass fractions of NASICON inorganic solid electrolyte Na3Zr2Si2PO4 were added to the electrode material. 12 Prepare several portions of slurry, and then coat several portions of slurry layer by layer on the current collector to make the NASICON inorganic solid electrolyte Na3Zr2Si2PO 12 The amount of addition decreases gradually from the direction close to the current collector to the direction away from the current collector, and then the electrode is dried, rolled, and cut to obtain an electrode. An electrolyte precursor solution containing a cyclic ether monomer and an initiator is injected into the electrode to form a gradient distributed NASICON-type inorganic solid electrolyte Na3Zr2Si2PO 12 The reaction between the initiator and the cyclic ether monomer is inhibited to realize the gradient polymerization of the cyclic ether-based polymer electrolyte in the electrode, thereby obtaining a gradient polymerized solid-state battery electrode.

2. The preparation method according to claim 1, characterized in that: The NASICON type inorganic solid electrolyte Na3Zr2Si2PO 12 The mass range of the gradient distribution in the electrode material from close to the current collector to far away from the current collector is 0.1wt-2wt%.

3. The preparation method according to claim 1, characterized in that: The cyclic ether monomers include one or more combinations of tetrahydrofuran, 1,3-dioxolane, 1,3,5-trioxane, 1,3-dioxane, epoxy-terminated linear siloxane and epoxy-terminated cage-type polysilsesquioxane.

4. The preparation method according to claim 1, characterized in that: The initiator includes a combination of one or more of a sodium salt initiator, a lithium salt initiator, an aluminum salt initiator, a tin salt initiator, a zinc salt initiator, a magnesium salt initiator, and a scandium salt initiator.

5. The preparation method according to claim 1, characterized in that: The cyclic ether monomer accounts for 40%-80% of the volume of the electrolyte.

6. The preparation method according to claim 1, characterized in that: The concentration of the initiator in the electrolyte is 0.1-1 mol / L.

7. The preparation method according to claim 1, characterized in that: The electrode material comprises an active material, a conductive agent and a binder which are uniformly mixed.

8. The preparation method according to claim 1, characterized in that: The electrolyte precursor solution also includes a solvent, an ion salt and an additive, and the ion salt is a lithium salt, a sodium salt or a potassium salt.

9. The preparation method according to claim 1, characterized in that: After the electrolyte precursor solution is injected into the electrode, it is left to stand at room temperature or under heating conditions. The cyclic ether monomer undergoes ring-opening polymerization under the action of the initiator, and a gradient-distributed NASICON-type inorganic solid electrolyte Na3Zr2Si2PO 12 The initiation effect of the initiator is suppressed to realize the gradient polymerization of the cyclic ether-based polymer electrolyte in the electrode.

10. An application of a solid-state battery electrode prepared by the preparation method according to any one of claims 1 to 9, characterized in that: The solid-state battery electrode is applied to the positive electrode and / or negative electrode of a lithium ion battery, the positive electrode and / or negative electrode of a sodium ion battery, or the positive electrode and / or negative electrode of a potassium ion battery.

Citation Information

Patent Citations

  • All-solid-state lithium ion battery and preparation method thereof

    CN108063278A

  • Preparation method of high-specific-energy composite solid positive electrode

    CN115312776A

  • In-situ solid-state battery and preparation method thereof

    CN119029361A

  • Electrode and electrolyte additives for high energy lithium-ion batteries

    US20230030959A1

Cited By

  • Composite ceramic electrolyte, all-solid-state sodium battery and preparation method and application of all-solid-state sodium battery

    CN121292963A